1985
DOI: 10.1177/0148607185009006671
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Branched‐Chain Amino Acid Formula Versus a Casein‐Based Supplement in the Treatment of Cirrhosis

Abstract: An orally administered branched-chain amino acid (BCAA) rich supplement (T), Travasorb-Hepatic was compared to a casein based supplement (E), Ensure, in a randomized double-blind cross-over study in eight malnourished, stable cirrhotics unable to achieve a daily dietary protein intake of 1.0 g/kg. Doses of antiportal systemic encephalopathy drugs remained constant and a baseline 1000 kcal, 40 g dietary protein intake was encouraged. To this diet, supplemental protein was added in daily 20-g increments to a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Since the 1970's, multiple studies have been done that have proven that protein restriction is not beneficial in HE; a summary of these studies can be found in table 1 [24,[36][37][38][39][40][41][42][43][44][45] . As far back as 1977,…”
Section: Effects Of Protein Restrictions On Progression Of Liver Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Since the 1970's, multiple studies have been done that have proven that protein restriction is not beneficial in HE; a summary of these studies can be found in table 1 [24,[36][37][38][39][40][41][42][43][44][45] . As far back as 1977,…”
Section: Effects Of Protein Restrictions On Progression Of Liver Diseasementioning
confidence: 99%
“…Compared to control groups consuming 40 g of protein, the higher intake of protein did not result in increased progression of liver failure or incidence Iiames J et al . Protein in older cirrhotic adults of HE [37][38][39][40] . Similar studies continued in the 1990's, showing that higher amounts of protein intake do not lead to worsening of hepatic encephalopathy [41,42,45] .…”
Section: Effects Of Protein Restrictions On Progression Of Liver Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…120 (c) In patients with frank encephalopathy, two crossover trials could not demonstrate that such individuals tolerated increasing amounts of BCAAs any better than other nitrogen sources. 118,119 (d) In patients with latent encephalopathy, one group 110 and one crossover 115 study showed better tolerance for the increasing amounts of BCAAs, but this ®nding could not be duplicated in one other group 113 and four crossover 117,118,121,122 experiments. Hence, it is dif®cult at this time to support the use of oral BCAAs in patients with liver disease.…”
Section: ±107mentioning
confidence: 99%